1975
DOI: 10.1111/j.1365-2141.1975.tb01863.x
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Group I and i Antigens of Amniotic Fluid

Abstract: Human amniotic fluid has been shown to contain blood group i as well as I antigens. Crude extracts of amniotic fluids at 16-23 weeks of gestation were in general more active than those obtained at term. A pool of amniotic fluids which had A, B, H as well as I and i activity was fractionated with an insolubilized anti-I (Group 3 type) immunoadsorbent column. There was evidence for the occurrence of I and i determinants on macromolecules carrying A, B and H determinants, for the fraction specifically retained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The details of the method will be described elsewhere. Briefly, a glycoprotein-rich extract was prepared from a sample of human meconium by digestion with pepsin and precipitation with ethanol as described by Feizi et al (1975). The extract was labelled with 1251 by the chloramine-T method (Greenwood et al, 1963) and enriched for blood-group-I and -i activities by affinity chromatography on an adsorbent made with an anti-(blood-group I) antibody coupled to Sepharose 2B .…”
Section: Immunological Analysismentioning
confidence: 99%
“…The details of the method will be described elsewhere. Briefly, a glycoprotein-rich extract was prepared from a sample of human meconium by digestion with pepsin and precipitation with ethanol as described by Feizi et al (1975). The extract was labelled with 1251 by the chloramine-T method (Greenwood et al, 1963) and enriched for blood-group-I and -i activities by affinity chromatography on an adsorbent made with an anti-(blood-group I) antibody coupled to Sepharose 2B .…”
Section: Immunological Analysismentioning
confidence: 99%
“…respectively) in 6ml ofequilibration buffer (10mM-Tris/HCl, pH 8.2, containing 1 % Empigen, 0.02% SDS, 0.1 % bovine serum albumin and 0.02,% sodium azide) was passed through an anti-(blood-group I) or a control column. The former contained 50mg of antibody (a macroglobulin) isolated from the serum of a patient (Low) and coupled to 5rml of Sepharose 2B as described by Feizi et al (1975), The control adsorbent contained 50mg of a Waldenstrom macroglobulin without anti-(blood-group I) activity. Adsorption was carried out at 4°C (flow rate, 2ml/h); unbound material was removed by washing with equilibration buffer at 4°C (flow rate, 40m1/h); bound material was eluted in two steps by washing with (1) equilibration buffer at 37°C and (2) equilibration buffer containing I M-NaI at 4°C.…”
Section: Vol 173mentioning
confidence: 99%
“…Preparation of glycoprotein extracts from stomach mucosae Fresh adult sheep stomachs (abomasa) were obtained at slaughter from a local abattoir. Glycoprotein-rich extracts of the mucosal scrapings from individual stomachs were prepared after digestion with pepsin as described previously (Bendich et al, 1946;Feizi et al, 1975). Aqueous solutions thus obtained were extracted twice with 2vol.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies with blood-group substances (Lloyd & Kabat, 1968) have indicated that one cycle of Smith degradation results in the destruction of only the terminal monosaccharides (also subterminal galactose residues in blood-group-H substance).Thus the following predictions would apply: terminal (non-reducing) galactose residues of precursor chains, terminal fucose and N-acetylgalactosamine residues of blood-group-A substances, and terminal fucose residues and subterminal galactose residues of blood-group-H substances would be destroyed. Affinity chromatography ofsheep glycoproteins An adsorbent made from the anti-(blood group I) antibody of patient Low was as described by Feizi et al (1975), and contained approx. 850mg of antibody protein coupled to 85 ml of Sepharose 4B.…”
Section: Smith Degradation Ofsheep Glycoproteinsmentioning
confidence: 99%